Answer:
for the first one, simply add g(x) and h(x) :
x+3 + 4x+1 = 5x + 4
the second one, you would multiply them :
(x+3)(4x+1) = 4x^2 + 13x + 3
the last one, you would subtract :
(x+3)-(4x+1) = -3x + 2
and then substitute 2 for 'x' :
-3*2 + 2 = -6 + 2 = -4
The third term is 9
t(3)=2(3)+3
6+3 = 9
Answer:
(-5,3)
Step-by-step explanation:
The point (5,7) translated down 4 units gets to the point (5,3). If you reflect it over the y-axis, the x-coordinate becomes negative, and the y-coordinate stays the same. This gets you the point (-5,3)
Hope it helps and is correct!
For (11, 1): (11 + 3)1 = 14(1) = 14
For (5, 2): (5 + 3)2 = 8(2) = 16 ≠ 14
For (7, 2): (7 + 3)2 = 10(2) = 20 ≠ 14
For (3, 2): (3 + 3)2 = 6(2) = 12 ≠ 14
Therefore, (11, 1) is a solution to this equation.
A = 5,460B = 5,733C = 7,280D = 6,720E = 8,050